Interactive effects of Leucaena leucocephala with low doses of lime on growth and yield of rice in acid sulphate soil - Tran Thi Ba; Upasena, S .H.; Sumitra Poovarodom; Salokhe, Vilas M.; Okumenishes Studienwerk Ecumenical Scholarship Programme (Bread for the World Organization) (Bangkok : Asian Institute of Technology, 1995)
A field experiment with low land rice was conducted in the acid sulphate soil of Bangkok Plain during the dry season (January-May) of 1995 to assess the response of rice to low rates of liming and green manuring. Seven levels of lime (0.00, 0.40, 0.80, 1.60, 3.20, 6.40 and 8.75 t ha-1 ) and two levels of green manure (0.0 and 7.5 t green leaf of Leucaena ha-1 ) were applied to the field 2 weeks before sowing the rice. The experiment was laid out as a randomized complete block design with 4 replications. Generally, liming alone, green manuring alone or the combination of both treatments are enough for improving grain yield. However, single lime or green manure application on this soil showed significantly positive effect on plant height, 1000 grain weight, the yield of grain, straw, total biomass and N uptake by straw, total uptake. Liming also showed increasing of soil pH and N uptake by grain. In contrast green manuring increased organic matter, percentage of N and residual N in the soil . Grain yield and N uptake by grain with low doses of lime with 3.2 t ha 1 was not significantly different than higher application of lime (up to 8.75 t ha- 1 ) but significantly higher than the control treatment. Grain yield with 7.5 t ha- 1 green manure (115 kg N ha 1 equivalent) was also significantly higher than without green manure treatment. Lime and green manure interaction significantly increased grain yield, total biomass yield and showed the response of low lime dose (1.6 t ha 1 ) with green manure application was the best treatment which was applied to rice. The differences of soil pH were significantly and linearly related to lime application levels, the grain yields were also significantly and linearly related to soil pH and N uptake by grain. In economic terms, control treatment was the highest compared to treatments of lime or green manure application alone or the combination of both. Only liming treatments were the most profitable, however, liming at different levels with green manure were found negative in profit
A Thesis Submitted in Partial Fulfillment of the Requirement for the degree of Master of Science, School of Environment, Resources, and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1995
Keywords: Rice -- Soils; Liming of soils